New fired bricks based on municipal solid waste incinerator bottom ash. Issue 10 (October 2017) - Taurino, R; Karamanova, E; Barbieri, L; Atanasova-Vladimirova, S; Andreola, F; Karamanov, A
The main objective of this work was to study the sintering process and technological properties of new fired bricks based on high amount of post-treated municipal solid waste incinerator bottom ash and refractory clay. In addition, the effect of the minor addition of flux (Na2 CO3 ) or reinforce (corundum) was also highlighted. Several methods were used to study the effect of compositions variations on the sintering process, structure and the mechanical characteristics of the test briquettes. Differential thermal analysis (TG/DTA) and dilatometry techniques were applied to study the thermal behaviour while scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy and high-temperature X-ray diffraction were used to elucidate the structure and the phase composition. The mechanical characteristics were estimated by micro-indentation, strength and various physical tests (porosity, linear shrinkage and water absorption, etc). The results highlight the possibility to use very high amount of municipal solid waste incinerator bottom ashes in the production of new fired bricks with good performances at all levels. It is also shown that the addition of additives managed the final properties, affecting the crystal phase formation, porosity and greatly the strength of the samples.